Promoting organic food production through flagship regions. Issue 1 (28th March 2022) - Mennig, Philipp; Sauer, Johannes
Abstract: Mitigating the environmental impact of agriculture is a major issue in negotiations on the future of the European Union's Common Agricultural Policy. Organic farming is commonly put forward in these discussions as a promising way to reduce the negative environmental impact of agriculture. Consequently, different promotional strategies aiming at the adoption of organic farming practices have been developed. In 2013, the German federal state of Bavaria initiated an innovative programme that resulted in 'organic flagship regions' being appointed in the years that followed. These regions are allocated support with the main goal of motivating farmers to switch to organic production. By applying a difference-in-differences estimator, we evaluate whether the programme has achieved its aims, i.e. whether more farmers have adopted organic farming practices within the flagship regions as compared to farmers outside such regions. The Theory of Planned Behaviour provides the conceptual framework to identify the main factors influencing a farmer's decision to go organic. Our results suggest that the programme fails to motivate farmers to switch to organic production and that there is a need to more effectively target decision-influencing factors.